Biotransformation of curcumin by Streptomyces sp. K1-18 isolated from mangrove soil - Aminudin, Nurul Iman; Wan Jaafar, Wan Muhammad Shafiq; Mohd Amin, Nurul Mehiran Shafikah; Kamarul Baharin, Raudah; Zainal Abidin, Zaima Azira (Taylor & Francis, 2025)
Biotransformation is recognised as a green chemistry tool to synthesise diverse natural product analogues for valorisation of their chemistry and bioactivities. It offers significant benefits compared to chemical synthesis, given its cost-effectiveness and greater selectivity. In this work, a curcumin analogue, namely gingerenone A, was yielded from the biotransformation process catalysed by Streptomyces sp. K1-18. The structure of the compound was established by using mass spectrometry/mass spectrometry chemical profiling assisted with in silico fragmentation by MetFrag tool. This biotransformation successfully afforded a reduction reaction on curcumin. This is the first report on utilisation of Streptomyces sp. K1-18 as a biocatalyst for biotransformation of curcumin.